Volume-Conducted Origin of the Field Potential at the Lateral Habenula - Bertone-Cueto, Nicolas Iván; Makarova, Julia; Mosqueira, Alejo; García-Violini, Demian; Sánchez-Peña, Ricardo; Herreras, Oscar; Belluscio, Mariano; Piriz, Joaquin (Frontiers in Systems Neuroscience, 2020)
Field Potentials (FP) are easily reached signals that provide information about the brain’s processing. However, FP should be interpreted cautiously since their biophysical bases are complex. The lateral habenula (LHb) is a brain structure involved in the encoding of aversive motivational values. Previous work indicates that the activity of the LHb is relevant for hippocampal-dependent learning. Moreover, it has been proposed that the interaction of the LHb with the hippocampal network is evidenced by the synchronization of LHb and hippocampal FPs during theta rhythm. However, the origin of the habenular FP has not been analyzed. Hence, its validity as a measurement of LHb activity has not been proven. In this work, we used electrophysiological recordings in anesthetized rats and feed-forward modeling to investigate biophysical basis of the FP recorded in the LHb. Our results indicate that the FP in the LHb during theta rhythm is a volume-conducted signal from the hippocampus. This result highlight that FPs must be thoroughly analyzed prior to its biological interpretation and argues against the use of the habenular FP signal as a readout of the activity of the LHb.